Improving Efficiency of Cooling Coil Chiller Units - Md. Garib Nawaj; Dr. M.K. Rath (International Journal of Engineering and Management Research, 2019)
Air Cooled condensers were first introduced in US power industry in early 1970’s, but only during last 10-15 years number of installations greatly increased largely due to growing attention being paid to environmental safety. Also, growing demand for water for both domestic and industrial use has brought an increased interest in use of Air Cooled condensers. This is a review paper which studies the performance of Air-cooled condenser under various operating conditions it is found that there is degradation in performance of air cooled condenser under high ambient temperatures and windy conditions. The heat rejection rate of ACC also depends on surface condition of fins and thus its performance is reduced due to external fouling of finned tubes due to weather conditions and by internal fouling from condensate (Ammonia corrosion). A Hybrid (dry/wet) dephlegmator achieves major enhancement in performance when ambient temperatures are high. Also shading of condensers is done for air-conditioning units to mitigate the adverse effect of high ambient temperatures due to solar radiation. Now a day’s wind walls are used to reduce the effect of high wind velocity .second option is to increase the fan speed Fin cleaning plays an important role in heat rejection. External cleaning improves air side heat transfer coefficient. In order to improve the performance of an ACC Flat tubes inclined at some angle to horizontal can also be used in place of conventional circular horizontal tubes so that an improvement in heat transfer rate occurs.